Dual Hydrogen- and Oxygen-Transport Membrane Reactor for Solar-Driven Syngas Production - Tou, Maria; Grylka, Adrian; Schuller, Arnaud; Bulfin, Brendan; Steinfeld, Aldo; Michalsky, Ronald (Frontiers in Energy Research, 2020)
A novel thermochemical dual-membrane reactor is considered with the goal of efficiently converting CO2 to fuels using concentrated solar energy as the process heat source. In contrast to the temperature-swing redox cycle, in this isothermal system the thermolysis of H2O at above 1,800 K is assisted by removal of O2 across an oxygen-permeable membrane and of H2 across a hydrogen-permeable membrane. The latter is consumed by a stream of CO2via the reverse water-gas shift reaction to re-form H2O and continuously generate CO. The net reaction is the splitting of CO2 to CO and 12O2. Because reactions at such high temperature are expected to be thermodynamically controlled, thermodynamic models are developed to calculate the equilibrium limits of the proposed dual-membrane configuration. For comparison, two reference configurations comprising either a single oxygen-permeable membrane or a single hydrogen-permeable membrane are analyzed. At 1,800 K, 1 bar total pressure, and (not applicable for the hydrogen-membrane reactor) 10 Pa O2, the equilibrium mole fraction of fuel is 2% with a single oxygen membrane, 4% with a single hydrogen membrane, and 15% in the dual-membrane system. In all cases, total selectivity of CO2 to CO and O2 is obtained. Assuming thermodynamic equilibrium, the solar-to-fuel energy efficiency realistically attainable is 4% with a single oxygen membrane, 8% with a single hydrogen membrane, and 17% in the dual-membrane configuration at the aforementioned conditions. By increasing the pressure of the feed of steam to 100 bar, the dual-membrane model system could theoretically approach full mass conversion of CO2 and reach up to 26% solar-to-fuel energy efficiency. However, developing appropriate and stable ceramic materials for such a system poses a significant challenge.